Human Cytomegalovirus Antigens in Malignant Gliomas as Targets for Adoptive Cellular Therapy - Landi, Daniel; Hegde, Meenakshi; Ahmed, Nabil (Frontiers in Oncology, 2014)
Malignant gliomas are the most common primary brain tumor in adults, with over 12,000 new cases diagnosed in the United States each year. Over the last decade, investigators have reliably identified human cytomegalovirus (HCMV) proteins, nucleic acids, and virions in most high-grade gliomas, including glioblastoma (GBM). This discovery is significant because human cytomegalovirus gene products can be targeted by immune-based therapies. In this review, we describe the current level of understanding regarding the presence and role in pathogenesis of HCMV in GBM. We describe our success detecting and expanding HCMV-specific cytotoxic T lymphocytes to kill GBM cells and explain how these cells can be used as a platform for enhanced cellular therapies. We discuss alternative approaches that capitalize on HCMV infection to treat patients with HCMV-positive tumors. Adoptive cellular therapy for HCMV-positive GBM has been tried in a small number of patients with some benefit, but we reason why, to date, these approaches generally fail to generate long-term remission or cure. We conjecture how cellular therapy for GBM can be improved and describe the barriers that must be overcome to cure these patients.